2016
DOI: 10.1002/bmc.3768
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS/MS determination and interaction of the main components from the traditional Chinese drug pair Danshen–Sanqi based on rat intestinal absorption

Abstract: The Chinese drug pair Danshen (Salvia miltiorrhiza)-Sanqi (Panax ginseng) has been widely used for centuries treating various cardiovascular disorders, among which salvianlic acid B (SAB), ginsenoside Rg (GRg ), ginsenoside Rb (GRb ) and notoginsenoside R (NGR ) were identified as the major components. The present study focused on the interaction between these components based on investigating their intestinal absorption using the Ussing chamber technique. The concentrations of SAB, GRg , GRb1 and NGR in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Ginsenoside Rg 1 and emodin were purchased from the National Institutes for Food and Drug Control (Beijing, China). Krebs’ Ringer bicarbonate (KRB) buffer is composed by 114 mM NaCl, 10 mM Glucose, 1.25 mM CaCl 2 ⋅2H 2 O, 1.1 mM MgCl 2 ⋅6H 2 O, 5.03 mM KCl, 0.30 mM NaH 2 PO 4 ⋅H 2 O,1.65 mM Na 2 HPO 4 , and 25 mM NaHCO 3 of pH 6.5 ( Huang et al, 2016 ). Solvents were of HPLC grade and other chemicals used were of analytical grade.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenoside Rg 1 and emodin were purchased from the National Institutes for Food and Drug Control (Beijing, China). Krebs’ Ringer bicarbonate (KRB) buffer is composed by 114 mM NaCl, 10 mM Glucose, 1.25 mM CaCl 2 ⋅2H 2 O, 1.1 mM MgCl 2 ⋅6H 2 O, 5.03 mM KCl, 0.30 mM NaH 2 PO 4 ⋅H 2 O,1.65 mM Na 2 HPO 4 , and 25 mM NaHCO 3 of pH 6.5 ( Huang et al, 2016 ). Solvents were of HPLC grade and other chemicals used were of analytical grade.…”
Section: Methodsmentioning
confidence: 99%
“…The Q (accumulative quantity), P app (apparent permeability), E r (efflux ratio), P r ( P app ratio), and E rr ( E r ratio) across the excited rat intestinal segments in the Ussing chamber were calculated using the following equations ( Li et al, 2012 ; Huang et al, 2016 ):…”
Section: Methodsmentioning
confidence: 99%
“…LC-MS is preferably employed to measure the plasma concentrations of ginsenosides, 371–374 and further investigate the mechanism of drug interactions. The reported mechanisms mainly involve the mediation of the absorption of ginseng in vivo , 371,375–378 the modulation of gut microbiota composition, 379–381 and the high affinity for drug transporters and cells, 379,382 the induction or inhibition of the CYP450 enzyme activities, 383 as well as the occurrence of DDI by measuring the PK parameters (such as C max , AUC, t max , and t 1/2 ) of ginseng drugs in vivo . 372–374,384,385…”
Section: Metabolism and Metabolomicsmentioning
confidence: 99%
“…To some extent, this explains the essence of the compatibility mechanism of TCM compound prescription. 380…”
Section: Metabolism and Metabolomicsmentioning
confidence: 99%
“…The coadministration of Danshen and Sanqi significantly improved intestinal absorption (2-fold) of the bioactive component salvianolic acid B in rats compared to administration of Danshen alone, suggesting synergistic effect of these two herbs [80]. However, another rat study reported oral administration of Fufang Danshen preparation or salvianolic acid B extract alone or in the presence of Sanqi, Borneol, and tanshinones extract had the same salvianolic acid B pharmacokinetics.…”
Section: Pharmacokinetic Alterations Of Danshen Bioactive Constitumentioning
confidence: 99%